Системные функции государственного управления региональным инвестиционным проектом (Путеводитель предпринимателя)
This article analyzes the investment resources and opportunities of industries and regions in defining the role and functions of domestic, foreign investors and regional authorities in the development of investment projects. The author examines the issues that are not sufficiently considered in the study of public investment management, such as: Systemic and situational approaches to investment management, tactical and strategic management of investment activities, the impact of external and internal environment on the system of investment management, efficiency of public investment management, and methods of analysis and evaluation of the effectvnosti investment management. Much attention is devoted to the experience of developed countries to create corporations and economic development areas (public or mixed). Analyzed as they are sent to the regional development of their capital and attract other investors, acting as a guarantor of effective investments in joint implementation of the project, as these corporations form of special funds through equity firmsLocated in the territory, as a means of funds directed to the construction needed for the city or area of residential and business complex with shops, restaurants, hotels, etc. As a conclusion the author offers organizational and economic and methodological principles of government investment, based on a systemic approach and cross-sectoral integration in the development and implementation of regional investment projects of domestic and foreign investorsThat can effectively address the problems and develop the economy of individual regions and municipalities